PEMETAAN DAERAH RAWAN LONGSOR WILAYAH DAS TANGNGA DENGAN SISTEM INFORMASI GEOGRAFIS - Nasiah Nasiah; Hasriyanti Hasriyanti; Andi Irhamiah (Jurnal Environmental Science, 2022)
ABSTRACTCurrently, the number of damaged watersheds has not improved, as evidenced by the increasing incidence of natural disasters such as landslides, floods and droughts. Much work has been done to restore the watershed, but no significant results have been achieved. This type of research is quantitative descriptive using geographic information system (GIS) software analysis program, in the form of overlay analysis, factors that affect rock types, rainfall, slope, soil movement susceptibility, soil texture, and land use. Based on the estimation results of landslide susceptibility in the Tangnga watershed, three levels of landslide susceptibility were obtained, namely: non-prone with an area of 4,562 ha (55%) with distribution in Uluere, Bantaeng, Sinoa, Eremarasa, and Bissapu districts downstream of the Tangnga watershed. The level of vulnerability with an area of 3,246 Ha (39%) has a distribution in Uluere, Bantaeng, Bissapu, and Eremarasa Districts. And the level of vulnerability is very vulnerable with an area of 449 Ha (6%) having a distribution in the upstream Tagnga watershed, namely Uluere, Bantaeng, Eremarasa, and Sinoa Districts.